Front Cover: Synthesis and Avidin Binding of Ruthenium Complexes Functionalized with a Light‐Cleavable Free Biotin Moiety (Eur. J. Inorg. Chem. 37/2018). Issue 37 (1st October 2018) - Siewert, Bianka; Langerman, Michiel; Pannwitz, Andrea; Bonnet, Sylvestre
Abstract : The Front Cover shows a streptavidin molecule functionalized with a light‐sensitive Ru–polypyridyl complex via a bis‐biotin ligand. One biotin is free and strongly interacts with the protein pocket, while the other is coordinated to ruthenium to hold the complex onto the protein in the dark. Upon blue light irradiation, the bond between the coordinated biotin and Ru is broken, which releases the Ru complex in solution. The synthesis and light cleavage strategy proposed in the article is a new step towards the use of streptavidin for cancer cell targeting of Ru‐based photoactivated chemotherapy. More information can be found in theFull Paper by S. Bonnet et al. For more on the story behind the cover research, see theCover Profile .